The hours of the virgin [large type] - Estleman, Loren D. (Estleman, Loren D. Amos Walker novels., 1999)
Detroit is no place for virgins, or gentlemen. Walker, who is neither, follows the 50-year-old trail of a stolen manuscript across the bleak landscape of a dead city, coming face to face with the man who murdered his partner 20 years ago.